Application of the logical framework methodology (MML) in the research seedbed projects of a distance university - Medina - López, Juan Carlos; Hurtado - Flórez, Dione Andrea; Barreda - Ramírez, Concepción (Universidad Francisco de Paula Santander, 2020)
This article shows the importance of MML and the application of this methodology by research seedbeds in the south-central zone -ZCSUR of a remote University. The research makes an inventory of all the seedbeds of the University in the area, determines each one of the theoretical aspects of the MML and investigates by means of a survey carried out on the 30 seedbeds of the Central South area, on different methodology and techniques that guide the work of the seedbed, taking as a reference the logical framework matrix (MML). It was found that the performance of the seedbeds is deficient in the use of methodologies such as the MML and a comparison is made between what is done or what should be done highlighting the advantages that the application of the methodology brings for the increase in production and effectiveness of research hotbeds.